Responsivitas dan Omni Channel Service Berpengaruh terhadap Kepuasan Pelayanan Masyarakat di Kantor Desa Ngreco Kecamatan Weru Kabupaten Sukoharjo - Azzahra Salsa Nabila; Indra Hastuti; Agus Suyatno (Jurnal Manajemen Riset Inovasi, 2026)
Advancements in information and communication technology in the digital era have transformed public service delivery into a more modern, efficient, and integrated system, encouraging government institutions to adopt digital innovations that improve accessibility and service quality. This study aims to analyze the relationship between responsiveness and omnichannel services and the public's decision to utilize services at the Ngreco Village Office in Weru District, Sukoharjo Regency. The study employs a quantitative approach using an associative research method to examine the influence of the independent variables on service utilization decisions. Data were collected through online questionnaires distributed to 67 respondents from the Ngreco Village community who had experience accessing public services. The collected data were analyzed using multiple linear regression to determine both the partial and simultaneous effects of responsiveness and omnichannel services. The results indicate that responsiveness and omnichannel services have a positive and significant influence on public service decisions, both individually and simultaneously. These findings suggest that improving service responsiveness and integrating various communication channels can enhance public trust, satisfaction, and service utilization. The study is expected to serve as a reference for the village government in improving service quality to be more responsive, integrated, effective, and oriented toward the evolving needs and expectations of the community.